1β–OH–arenobufagin induces mitochondrial apoptosis in hepatocellular carcinoma through the suppression of mTOR signaling pathway. (10th February 2021) - Deng, Li-Juan; Lei, Yu-He; Quan, Jing-Yu; Li, Bao-Jing; Zhang, Dong-Mei; Tian, Hai-Yan; Chen, Ye; Zhang, En-Xin; Chen, Lei; Ye, Wen-Cai; Ning, Wei-Min; Yu, Lin-Zhong; et al.
Abstract: Ethnopharmacological relevance: Chansu, dried secretions from Bufonidae, has long been used for cancer treatment as a traditional Chinese medicine. In searching for effective anti-hepatoma agents from Chansu, our preliminary drug screening found that a bufadienolide, namely 1β-hydroxyl-arenobufagin (1β–OH–ABF), displays anti-hepatoma activities. However, the anti-hepatoma effects and molecular mechanisms of 1β–OH–ABF have not been defined. Aim of the study: To evaluate the anti-hepatoma activity of 1β–OH–ABF against liver cancer Hep3B and HepG2 cells in vitro and in vivo, as well as explore the underlying mechanisms. Materials and methods: The anti-proliferative effects of 1β–OH–ABF on liver cancer Hep3B, HepG2, HuH7, SK-HEP-1 and normal hepatocyte LO2 cells were examined by MTT assay and colony formation assay. Hoechst 33258 staining and Annexin V-FITC/PI staining assay were used to analyze apoptosis induced by 1β–OH–ABF. The collapse of the mitochondrial membrane potential (ΔΨm) was detected by JC-1 staining assay. Western blotting was used to examine the expression levels of targeted proteins. The role of mTOR in 1β–OH–ABF-induced apoptosis was investigated using small interfering RNA (siRNA) transfection. Zebrafish xenograft model was established to evaluate the anti-hepatoma effects of 1β–OH–ABF in vivo . Results: We found that 1β–OH–ABF inhibits the proliferation of Hep3B, HepG2, HuH7, SK-HEP-1 cells but has little cytotoxicity towards LO2 cells. 1β–OH–ABF induces mitochondria dysfunction and triggers mitochondria apoptotic pathway, which is accompanied by the loss of ΔΨm, upregulation and translocation of Bax, as well as cleavages of caspase-9, caspase-3 and PARP. Mechanistically, 1β–OH–ABF markedly decreases the expression level of p-AKT/AKT and p-mTOR (Ser2248 and Ser2481)/mTOR in a time-dependent manner. Inhibition of mTOR by siRNA strengthens 1β–OH–ABF-mediated apoptosis. Critically, 1β–OH–ABF shows a marked in vivo anti-hepatoma effect on human Hep3B cell xenografts in zebrafish model. Conclusion: 1β–OH–ABF induces mitochondrial apoptosis through the suppression of mTOR signaling in vitro and in vivo, indicating that 1β–OH–ABF may serve as a potential agent for the treatment of liver cancer. Graphical abstract: Image 1